PENGARUH ISLAM DAN KEBUDAYAAN MELAYU TERHADAP KESENIAN MADIHIN MASYARAKAT BANJAR - Akmal, Atqo (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2018)
Banjaresse Culture is a transformation and transculturation of the pre-Islamic religious beliefs with post-Islamization. The contact between the two cultures resulted in a new Banjar entity that strongly influenced by the values of Islam and Malay culture. In art, madihin emerges as the result of assimilation between Malay-Muslim and Banjar art cultures. Madihin has similarities to the oral literature of Malay, pantun and verse, but it is delivered in Banjaresse language, with rhymes that are not necessarily follow certain pattern (eg: must be a-a-a-a or a-b-a-b), no limitation for number of stanza, and not play a particular drama. The emergence of madihin is a transformation of qasida form which present to mark the presence of Islam in the archiplego. The use of tarbang as a musical instrument in madihin, similar to qasida with its rebana-drums. However, madihin is different from the qasida arts whose lyrics are the verses of the song. Madihin is likely an oral literature that has no pattern of regular rhyme and lyric, and not too concerned with the suitability of the lyrics, verse with the rhythm, as an important conformity in the music of qasida.Budaya masyarakat Banjar merupakan transformasi dan transkulturasi religiusitas kepercayaan pra-Islam dengan paska islamisasi. Pertemuan keduanya menghasilkan suatu entitas Banjar baru yang dipengaruhi kuat oleh nilai dan ajaran Islam serta kebudayaan melayu. Dalam bidang kesenian, sastra lisan madihin muncul sebagai hasil dari asimilasi antara kebudayaan Melayu-Islam dan Banjar. Madihin memiliki kesamaan dengan sastra lisan melayu sejenis pantun dan syair, namun disampaikan dalam bahasa Banjar, dengan rima yang tidak mesti teratur (misalnya harus: a-a-a-a atau a-b-a-b), jumlah bait yang tidak baku, dan tidak melakonkan suatu drama tertentu. Kemunculan madihin merupakan transformasi bentuk qasida yang hadir ke nusantara saat berkembangnya Islam. Penggunaan tarbang sebagai instrumen musik pengiring dalam pertunjukkan madihin, mirip dengan kesenian qasida dengan gendang rebana-nya. Namun madihin berbeda dengan kesenian qasida yang liriknya merupakan bait-bait lagu, madihin merupakan penyampaian sastra lisan sejenis pantun dan syair yang dilagukan, serta tidak terlalu mementingkan kesesuaian bait lirik dengan irama, satu kesesuaian yang penting dalam musik qasida.